2023
DOI: 10.3390/biomedicines11020494
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Probiotics in Inducing and Maintaining Remission in Crohn’s Disease and Ulcerative Colitis: A Systematic Review of the Literature

Abstract: Crohn’s disease (CD) and ulcerative colitis (UC) are chronic inflammatory diseases of the gastrointestinal tract affecting millions of patients worldwide. The gut microbiome partly determines the pathogenesis of both diseases. Even though probiotics have been widely used as a potential treatment, their efficacy in inducing and maintaining remission is still controversial. Our study aims to review the present-day literature about the possible role of probiotics in treating inflammatory bowel diseases in adults.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Our systematic review was in congruence with systematic reviews of probiotics in adults with viral gastroenteritis [ 55 ] and IBDs (mostly in ulcerative colitis) [ 56 ]. However, several recent systematic reviews showed no or minimum beneficial effects of probiotics in Crohn’s disease [ 56 , 57 ]. Some study results showed mixed effects in terms of having benefits of using probiotics in reducing the risk of gastrointestinal infections (RR 0.86, 05% CI 0.73 to 1.101) but having no effects on the duration or severity of gastrointestinal infection.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our systematic review was in congruence with systematic reviews of probiotics in adults with viral gastroenteritis [ 55 ] and IBDs (mostly in ulcerative colitis) [ 56 ]. However, several recent systematic reviews showed no or minimum beneficial effects of probiotics in Crohn’s disease [ 56 , 57 ]. Some study results showed mixed effects in terms of having benefits of using probiotics in reducing the risk of gastrointestinal infections (RR 0.86, 05% CI 0.73 to 1.101) but having no effects on the duration or severity of gastrointestinal infection.…”
Section: Discussionmentioning
confidence: 70%
“…The authors cautioned use of the results due to a low number of studies, high risk of bias and heterogeneity in the studies [ 58 ]. The study results may be not comparable, partly because of differing outcome measures [ 58 ] and also not having results of a meta-analysis in all reported studies [ 56 , 57 ]. Further studies are suggested for understanding the effect of probiotics as a single therapy or in combination with standard treatments for Crohn’s disease and gastroenteritis due to other etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…To improve patients' general quality of life, this study emphasized the significance of treating psychological well-being in IBD care. Health status and sociodemographic characteristics have been linked to changes in IBD patients' health-related quality of life (HRQOL) [ 61 ]. The study examined HRQOL using the Inflammatory Bowel Disease Questionnaire (IBDQ) and emphasized the need to consider these variables when assessing patients' well-being.…”
Section: Reviewmentioning
confidence: 99%
“…Because probiotics help to restore the mucosa and promote anti-inflammatory effects, they considerably reduce intestinal inflammation when used as a treatment, eliminate discomfort and edema, and overall improve the quality of life. It’s also important to point out that probiotics are significantly less expensive and have less potential side effects than other forms of gastrointestinal inflammation treatment 3 . Combining probiotic strains with phenol-rich extract as antioxidants may be beneficial in extending their viability and providing health benefits to the host 4 .…”
Section: Introductionmentioning
confidence: 99%